Relationship Between Emotional Regulation and Resilience in Survivors of Sexual Violence in East Java - Clarista, Elza Mourine; Puspitasari, Dwi Nikmah (Universitas Negeri Malang, 2023)
This research aims to determine the relationship between emotional regulation and resilience in survivors of sexual violence in East Java. This research uses a quantitative method with the criteria being that respondents are survivors of sexual violence, whether male or female, aged 18‒25 years, domiciled in East Java, have experienced sexual violence, and have not currently experienced such an incident. The measuring instrument used in this research consists of an adapted results scale. Emotion regulation was measured using The Difficulty in Emotion Regulation Scale (DERS) from Gratz and Roemer (2004) with 33 items, and the resilience variable was measured using the resilience scale by Reivich and Shatté (2002) with 52 items with 103 respondents. The study findings indicate a significant and positive correlation (with a coefficient of 0.404) between emotional regulation and resilience in individuals who have survived sexual violence. In simpler terms, as emotional regulation improves, resilience also increases; conversely, if emotional regulation decreases, so does resilience.